Consumer morality and moral consumption behavior: literature domains, current contributions, and future research questions - Yaprak, Attila; Prince, Melvin (Journal of Consumer Marketing, 2019)
Purpose: The literature on consumer morality and consumption is spread widely across many research streams and would benefit from grouping under selected themes so that scholars’ work can be guided by the compass of these themes. It is also important to add studies to each of these themes to serve as gateways that will guide new research. The aim of this special issue of the Journal of Consumer Marketing was to achieve precisely this purpose. The purpose of this paper is to open the gate to the exploration of the themes that today describe this landscape. Design/methodology/approach: The paper assesses the contributions made in each of several domains to better understand, why and how moral consumption works, what its ingredients are and how it may grow in the future. There are at least four domains of morality and moral consumption studies as follows: the formation of the moral self and moral identity; moral identity and ethical consumption; moral reasoning (cognitive processes) and moral choice; and the moral self and marketing. Each of these domains of work provides insight into the moral consumption phenomenon. Findings: The authors highlight the development of the moral self and underscore the significance of the relationship between identity development and the individual’s moral actions and by extension the significance of that relationship in moral consumption. Also, the paper adds to the current discussion on morality and ethical consumption by underscoring their interlinked nature and how that linkage can drive consumption behavior, highlight the cognitive processes involved in moral choices and how consumers reason to arrive at those choices. Finally, the authors provide examples of the workings of moral identity and reasoning in consumption contexts more directly. Originality/value: Each of these morality and moral consumption domains of work provides unique insights into the moral consumption phenomenon; thus, it is important to disseminate the contributions made in each domain to better understand, why and how moral consumption works, what its ingredients are and how it may grow in the future. In this paper, the authors offer contemporary original samples of key contributions to each of these domains. © 2019, Emerald Publishing Limited.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-197-857-855-353, pop00162, yaprakConsumerMoralityMoral2019a tex.type: [object Object]
Keywords: Consumer morality; Ethical consumption; Moral choice; Moral consumption; Moral identity; Moral reasoning; dept.mkt; peer-reviewed